Complete Genome Sequence of Bacillus amyloliquefaciens Strain Co1-6, a Plant Growth-Promoting Rhizobacterium of Calendula officinalis - Köberl, Martina (Genome Announc, 2015)
The genome sequence of Bacillus amyloliquefaciens strain Co1-6, a plant growth-promoting rhizobacterium (PGPR) with broad-spectrum antagonistic activity against plant-pathogenic fungi, bacteria, and nematodes, consists of a single 3.9-Mb circular chromosome. The genome reveals genes putatively responsible for its promising biocontrol and PGP properties.